Penerapan Fitur Firebase Cloud Messaging Pada Sistem Kontrol Pembayaran Iuran BPJS Ketenagakerjaan Berbasis Mobile - Meidina, Mita; Junadhi, Junadhi; Rio, Unang; Efendi, Yoyon (Forum Kerjasama Pendidikan Tinggi, 2022)
BPJS of Employment is the organizer of a social security program that functions to protect workers through four employment social security programs, namely Work Accident Insurance, Old Age Security, Death Security, and Pension Security. Information regarding the payment of BPJS Employment Contributions is an important factor in supporting social security programs for workers and employees. This is because there are still many participants who are in arrears in payment of the BPJS Employment Contribution and there is no immediate information regarding the payment of the BPJS Employment Contribution. In this study, an application was made so that an administrator could send notification messages regarding the payment of the BPJS Employment Monthly Contribution to participants and could receive reports on the payment of contributions that have been made by participants. The system design this time was assisted by Firebase Cloud Messaging (FCM) technology which functions as a web service. Messages that have been sent can be stored in a database that can be viewed on the admin web page. The results of this study are successful in building a BPJS employment payment control application by implementing the mobile-based Firebase Cloud Messaging (FCM) feature. This application can send notifications to participants regarding due information on dues payments in real time. Makes it easier for participants to get the latest information quickly. For the tests carried out using the functionality testing of the system by performing simulations on each function of the system made and concluded that the system functions can run well